A review of patterns and geographical distribution of human-wildlife conflicts in Indonesia - Farid Rifaie; Eko Sulistyadi; Yuli Sulistya Fitriana (The East Java Biological Society, 2021)
The unprecedented growth of human-dominated landscapes has led to population decline and the extinction of many animal species. A major paradigm shift that perceived wildlife as problem animals into threatened species that need protection triggered human-wildlife conflict studies. Although human-wildlife conflict incidences can be found globally, they have unique characteristics in each region of the world. However, little is known about the characteristics of human-wildlife conflicts in Southeast Asia, particularly Indonesia. There is a need for a comprehensive insight into human-wildlife conflict studies in Indonesia to understand past advancements and propose future priorities. This study examined the literature that provides the overall view of the human-wildlife conflict patterns in the country. The results showed that there was a comparatively small number of studies because this field was a relatively new subject in Indonesia. Furthermore, there were big gaps regarding animal species and the geographic distribution of study sites. A total of 35 species belonging to eight taxonomic groups experienced conflicts with humans. However, the studies heavily focused on three groups of animals and certain areas of the country. The predominant conflict sites were secondary forest, agroforestry, and farmlands. The conflicts in these areas unveiled the significance of local beliefs and social norms for formulating mitigation strategies.